Creating information about business processes of IT-company in management accounting - Papinko, Andrii (Herald of Economics, 2023)
Introduction. Formation of information about business processes in the management accounting system will help to avoid the deforming transformations of individual processes and sharp dynamic fluctuations in key business performance indicators. For a clear understanding of the need to optimize each process in the management accounting system, there is an opportunity to form a series of indicators that will demonstrate in real time the growth in business value and its real state. For IT companies, it is necessary to take into account the peculiarities of their organization and the construction of business processes, the identification of a series of indicators to identify «bottlenecks» and determine processes that need optimization and reengineering. The purpose of the study is to explore and analyze methods of creating information about business processes in IT companies.Research methods. To conduct scientific research in the article, the following were used: monographic analysis to study scientific works on the topic of research; critical analysis – assessment and comparison of approaches, methods, and results of previous studies; case study methodology – studying the practice of management accounting in IT companies; data analysis and statistical analysis, content analysis, and expert evaluations to obtain results.Results. The article highlights the processes of analysis and description of business processes, identification of key performance indicators, and integration of technologies for optimizing work. In the management accounting system, it is proposed to introduce a coefficient measure of business size, evaluate different product models, predict increases/decreases in efficiency, forecast the impact of the external environment, and form relevant information for managerial decision-making.Prospects. Promising directions for the development of research are issues of effective resource management, methodologies for systematic analysis of business processes, and improvement of strategic planning.